Biomonitoring of Human Exposure to Prestige Oil: Effects on DNA and Endocrine Parameters - Beatriz Pérez-Cadahfa; Josefina Méndez; Eduardo Pasaro; Anunciación Lafuente; Teresa Cabaleiro; Blanca Laffon (SAGE Publishing, 2008)
Since 1960, about 400 tankers spilled more than 377765 tons of oil, with the Prestige accident (Galician coast, NW Spain, November 2002) the most recent. Taking into account the consistent large number of individuals exposed to oil that exists all over the world, it seems surprising the absence in the literature of studies focused on the chronic effects of this exposure on human health. In this work we evaluated the level of DNA damage by means of comet assay, and the potential endocrine alterations (prolactin and cortisol) caused by Prestige oil exposure in a population of 180 individuals, classified in 3 groups according to the tasks performed, and 60 controls. Heavy metals in blood were determined as exposure biomarkers, obtaining significant increases of aluminum, nickel and lead in the exposed groups as compared to controls. Higher levels of genetic damage and endocrine alterations were also observed in the exposed population. DNA damage levels were influenced by age, sex, and the use of protective clothes, and prolactin concentrations by the last two factors. Surprisingly, the use of mask did not seem to protect individuals from genetic or endocrine alterations. Moreover, polymorphisms in genes encoding for the main enzymes involved in the metabolism of oil components were analyzed as susceptibility biomarkers. CYP1A1-3'UTR and EPHX1 codons 113 and 139 variant alleles were related to higher damage levels, while lower DNA damage was observed in GSTM1 and GSTT1 null individuals.